Utility of advertising for creativity education: an experimental study targeting school children. Issue 3 (4th May 2017) - Han, Kyoo-Hoon; Kim, Jieun
Abstract : This study investigated whether the Advertising-In-Education (hereafter AIE) program would influence the growth of creativity in elementary school students. AIE has been discussed by advertising scholars and used in some schools in South Korea since its inception approximately 10 years ago; yet, empirical research to prove its effect on education is rare. A field experiment using a pilot AIE program was implemented with third and fourth graders at two local elementary schools for 12 weeks. To measure the degree and significance of improvement in students' creative ability and creative personality, a series of pretests and posttests were administered using creativity measuring instruments. Results indicate that the AIE program has been effective in enhancing both creative ability and creative personality of elementary school students. Based on these results, several important implications were discussed and some directions for further research were suggested.